Didactic transposition: an example in the educative system in Costa Rica - Alfaro Carvajal, Cristian (2012)
This paper includes some fundamental ideas about the theory of didactic transposition of Yve Chevallard (1980), from which it is made an analysis of the knowledge transformation suffers from the mathematical level to the scholastic level. To demonstrate this transformation, it is analyzed the theme of integers, which is included in the seventh- grade curriculum of the educational system of Costa Rica.